Unexpected temporal localization of tuberculosis verrucosa cutis - Selami Aykut Temiz; İlkay Özer; Arzu Ataseven; Recep Dursun; Mustafa Cihat Avunduk (Galenos Publishing House, 2020)
Clinical forms of cutaneous tuberculosis (TB) which is a chronic granulomatous disease, varies by the route of entry into the body, the number of bacilli, its virulence and the immunological response of the body. TB verrucosa cutis (TBVC) occurs in patients who have previously been affected by tuberculosis bacilli with healthy immunity. A 68-year-old male patient was referred to our dermatology outpatient clinic from an external dermatology center with complaint of verrucous plaques on the left temporal region, persisting for two months. After a diagnosis of wart and seborrheic keratosis, cryosurgery and destructive procedures were applied to the lesions of the patient many times. Histopathological examination revealed granulomatous textures classified by infiltration of inflammatory cells around the keratin plugs and giant multinuclear cells in the epithelium sublayer, and positive staining with CD68 was detected in immunohistochemical examination. The patient was diagnosed with TBVC clinically and histopathologically. At the end of the anti-tuberculosis treatment, the lesions largely regressed with postinflammatory hyperpigmentation. Herein, we report a case of TBVC with unusual localization, which was initially misdiagnosed as wart and seborrheic keratosis. This case emphasizes the importance of differential diagnosis